The Influence of Wheat Flour and Tapioca Comparison Against Characteristics of The Chips Beluntas Leaves During Storage - Luh Suriati; I Nyoman Rudianta; Putu Candra; I Gusti Ayu Sukmawati (SEAS (Sustainable Environment Agricultural Science), 2017)
This study aims to know the comparison of wheat flour and tapioca flour in order to make the right ones not quickly wilted. Beluntas is herbs containing chemical compounds including i.e. phenol, alkaloids, tannins, essential oils that act as an antioxidant, anti-bacterial and also helps eliminate body odor. Leaf beluntas, when made into chips will be able to add diversification food products. Surely this will be very interesting for new innovations of food and expected to get the international market. Characteristics of the chips beluntas leaves can still be maintained with tapioca flour: comparison of 30:70 at 8 days storage with objective observations of water levels 21.50%, carbohydrates 8.74%, proteins 2.73%, fat 18.90%, levels of phenol 1485.33mg/kg drag power antioxidant 0.06%). While the subjective observations (color, aroma, flavor, texture and overall admissions) 6.0-6.7 with criteria like-love. Keywords: wheat flour, tapioca, chips beluntas, storage